The Response of Aluminium Foams Under Quasi-Static Loading - Said, M. R; Tan, CheeFai (Chiang Mai, 2008)
Aluminium foams are now being considered for use in lightweight structural sandwich panels such as aircraft body and in energy absorption systems for protection from impacts. In both cases, they may be subject to uniaxial and as well as biaxial loadings. In this study, the uniaxial loading at a rate of 5 mm/min was performed to find the crushing characteristics and their directional dependency. Eight specimens were used in uniaxial compression. The load responses were recorded and compared with the biaxial loading. Biaxial tests were conducted in a custom testing facility between rigid platens, which can be moved independently in two principles direction at the same speed. Five specimens in biaxial loading in various densities were used. Considerable enhancement in collapse loads and lead to higher energy absorption was seen in biaxially loaded metallic foams in comparison with uniaxial loading. The refined empirical relationship for uniaxial loading was also developed and was satisfactory well with the experiment.